THE PERCEPTIONS OF ENGLISH TEACHER AND PARENTS ON THE REMOVAL OF ENGLISH SUBJECT IN ELEMENTARY SCHOOL - Zildjian Saka Sulaiman (VISION, 2022)
This research was conducted from 25 September – 18 October 2021 which aimed to investigate the English teacher and Parents in Education case that is the removal English in elementary school as a subject. Semi-structured interviewed was used to collect the data then it was analyzed with semi structured interview. The researcher was found that both parties were disagree and disappoint with this regulation, because they concern about the children’s education further, such as the inability of students to achieve any English lesson in junior high school because they have lack in vocabulary whereas they are categorized as young learner that have good quality to remember vocabularies and they are lived in a tourism place. The limitation of economic and knowledge of parents become a barrier in this case make the school as the only one hope to learn English. Moreover the school party just delivered this regulation to the students in the classroom. It make all parents did not know about this regulation, an appropriate delivery of information is required in this case because they have the right and obligation in education based on law no 47 article 13.